Innovation in Nonbusiness Organizations from a Conceptual Point of View - Sándorfi, Gergő; Pataki, Béla (International Journal of Engineering and Management Sciences, 2021)
The definitions of innovation have been transformed a lot over time since Schumpeter introduced his concept. Even recently one of the most prestigious innovation management references, the Oslo Manual have changed its concept. One rarely discussed aspect of the concept of innovation is that most of the definitions are referring to the business sector; only a few of them are referring to any kinds of organizations, including non-profit and governmental organizations. Any kind of organization must innovate sooner or later; therefore they have to learn how to manage innovation effectively and efficiently. That is why the broad type of definitions is recommended, involving not only for-profit organizations but non-profit and governmental organizations as well.